2018
DOI: 10.1111/jog.13879
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean rates in a Chilean public hospital and the use of a new prioritization criteria: The relevance index

Abstract: Aim: Cesarean section rates are increasing worldwide and Robson's classification system allows a practical approach to study this phenomenon. C-section in Chile has been indicated as unexpectedly high, with important variability within the country and payment systems. The aim was to report our data using Robson's system and the evolution of local C-section rate in a public hospital during a 9-year period. Methods: Retrospective analysis (2005-April 2014), in a metropolitan hospital in Santiago. All deliveries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…When analyzing the groups with the greatest contribution to the overall CS rate, our results are in agreement with other studies worldwide, in which multiparous women with a history of at least 1 previous CS, gestational age ≥ 37 weeks, and in cephalic presentation (Group 5) are among the main contributors, 9 ranging from 17.2% in South Africa 10 11 12 13 to 35.6% of all CSs in Colombia. 10 These findings suggest that interventions to reduce the CS rate need to be implemented in Group 5, aiming to ascertain a VBAC; nevertheless, at the same time, the most important action should be preventing the first CS in women of Groups 1 to 4.…”
Section: Discussionsupporting
confidence: 91%
“…When analyzing the groups with the greatest contribution to the overall CS rate, our results are in agreement with other studies worldwide, in which multiparous women with a history of at least 1 previous CS, gestational age ≥ 37 weeks, and in cephalic presentation (Group 5) are among the main contributors, 9 ranging from 17.2% in South Africa 10 11 12 13 to 35.6% of all CSs in Colombia. 10 These findings suggest that interventions to reduce the CS rate need to be implemented in Group 5, aiming to ascertain a VBAC; nevertheless, at the same time, the most important action should be preventing the first CS in women of Groups 1 to 4.…”
Section: Discussionsupporting
confidence: 91%
“…Another Mexican study found an overall CSR ranging from 53.5 to 48.7% [ 15 ]. Only a Chilean facility-based study found lower rates (27%), despite drawing attention to the increase in C-sections in groups 1, 3 and 4, suggesting that in the following years the facility will probably face an increase in group 5 [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although birth timing is not consistently a modifiable risk factor, elective caesarean section can be. Elective caesarean sections are increasing in frequency in many countries 11,22‐24 due to multiple factors including convenience, reimbursement rates and patient request. This knowledge of the specific increased risk for the infants may aid in physician‐patient discussions about reducing elective caesarean sections during particular seasons.…”
Section: Discussionmentioning
confidence: 99%